Petroleum Product Pricing and Complementary Policies : Experience of 65 Developing Countries Since 2009 - Kojima, Masami (World Bank, Washington, DC, 2013)
Unable to cope fully with steadily climbing world oil prices since mid-2009, many of the 65 countries reviewed in this paper have progressed slowly or even reversed course in reforming pricing of petroleum products. End-user prices in July 2012 varied by two orders of magnitude across the countries. More than two-fifths, including some that had only recently adopted automatic pricing mechanisms, froze the prices of gasoline, diesel, or both for months or even years on end during the study period. When the prices were finally adjusted, the increases were sometimes substantial, leading to large-scale protests, partial or full reversals of price adjustments, or softening of pricing reform policy. Governments' attempts to keep domestic prices artificially low -- through price control, export or quantity restrictions, or political pressure put on oil companies -- have helped curb inflation in the short term, but frequently with serious negative consequences: flourishing black markets, smuggling, fuel adulteration, illegal diversion of subsidy funds, large financial losses suffered by fuel suppliers, deteriorating refining and other infrastructure, and acute fuel shortages causing economy-wide damage. In several countries, subsidies, price controls, and other restrictions have helped protect inefficient refineries and oil marketers. Mitigation responses have included fuel conservation programs; fuel diversification, particularly liquid biofuels to substitute gasoline and diesel; and efforts to lower costs of supply, including strengthening infrastructure, promoting price competition, hedging, negotiating price discounts with exporters, and bulk procurement. Various forms of assistance to consumers have also been offered, especially to households, agriculture, transport, and fisheries.